Metabolomic Profile of BALB/c Macrophages Infected with Leishmania amazonensis: Deciphering L-Arginine Metabolism - Muxel, Sandra Marcia (Int J Mol Sci, 2019)
Background: Leishmaniases are neglected tropical diseases that are caused by Leishmania, being endemic worldwide. L-arginine is an essential amino acid that is required for polyamines production on mammal cells. During Leishmania infection of macrophages, L-arginine is used by host and parasite arginase to produce polyamines, leading to parasite survival; or, by nitric oxide synthase 2 to produce nitric oxide leading to parasite killing. Here, we determined the metabolomic profile of BALB/c macrophages that were infected with L. amazonensis wild type or with L. amazonensis arginase knockout, correlating the regulation of L-arginine metabolism from both host and parasite. Methods: The metabolites of infected macrophages were analyzed by capillary electrophoresis coupled with mass spectrometry (CE-MS). The metabolic fingerprints analysis provided the dual profile from the host and parasite. Results: We observed increased levels of proline, glutamic acid, glutamine, L-arginine, ornithine, and putrescine in infected-L. amazonensis wild type macrophages, which indicated that this infection induces the polyamine production. Despite this, we observed reduced levels of ornithine, proline, and trypanothione in infected-L. amazonensis arginase knockout macrophages, indicating that this infection reduces the polyamine production. Conclusions: The metabolome fingerprint indicated that Leishmania infection alters the L-arginine/polyamines/trypanothione metabolism inside the host cell and the parasite arginase impacts on L-arginine metabolism and polyamine production, defining the infection fate.